Transition Metal Complexes of NHC Ligands Functionalized with the Cationic (η5‐Cyclopentadienyl)(η6‐phenyl)iron(II) Motif. Issue 16 (17th May 2022) - Malchau, Christian; Fries, Daniela V.; Mees, Yannick; Jakobs, Marisa F.; Sun, Yu; Becker, Sabine; Niedner‐Schatteburg, Gereon; Thiel, Werner R.
Abstract: Starting from [(η 5 ‐cyclopentadienyl)(η 6 ‐phenyl)iron(II)]imidazole, dicationic imidazolium salts were prepared by N ‐alkylation. Reaction of these compounds with basic metal precursors such as mesityl copper(I) or palladium(II) acetate led to mono respectively dicationic transition metal NHC complexes (NHC= N ‐heterocyclic carbene). Transmetalation using the copper(I) complexes opened up the access to NHC gold(I) compounds. PEPPSI‐type NHC complexes of palladium(II) and platinum(II) were prepared by offering a neutral pyridine ligand to the transition metal center. A rhodium(I) NHC complex was accessible by deprotonation of the dicationic imidazolium precursor and subsequent treatment with [(COD)Rh(μ 2 ‐Cl)]2 (COD=1, 5‐cyclooctadiene). The new NHC complexes were investigated by means of NMR spectroscopy, mass spectrometry as well as single crystal X‐ray structure analysis. Both, the palladium(II) containing PEPPSI‐type and the gold(I) complex, were investigated for their catalytic properties in typical model reactions such as cyclization reactions, Suzuki coupling and cyanation. In addition, a selenium adduct was synthesized in order to study the electronic properties of the underlying ligand backbone. Based on the chemical shift in the 77 Se NMR spectrum, it is evident that these NHC ligands possess rather poor π‐acidity. Abstract : A series of late transition metal complexes are accessible from electron‐poor NHC ligands functionalized by a cationic iron(II) sandwich complex.